Effects of SGLT-2 Inhibitors on Vascular Endothelial Function and Arterial Stiffness in Subjects With Type 2 Diabetes: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Wei, Ran; Wang, Weihao; Pan, Qi; Guo, Lixin (Frontiers in Endocrinology, 2022)
Abstract Objective: This systematic review and meta-analysis aimed to evaluate the effects of SGLT-2 inhibitors (SGLT-2i) on endothelial function and arteriosclerosis in diabetic patients. Methods: Randomized controlled trials (RCTs) were retrieved from PubMed, Embase, Cochrane Library, and Web of Science databases to evaluate the effects of SGLT-2i on endothelial function and atherosclerosis in type 2 diabetic patients. Results: We selected 11 RCTs involving 868 patients. Of these, six studies provided flow-mediated dilation (FMD) levels before and after the intervention. The pooled analysis showed that SGLT-2i could significantly improve the FMD compared to the control group (SMD: 0.18, 95% CI: 0.02 ~ 0.34, P = 0.03). Three studies provided the change in FMD before and after the intervention. Pooled analysis showed no significant differences in FMD change between the SGLT-2i group and the control group. (MD: 2.1, 95%-CI: -0.11~4.31, P = 0.06). Five studies showed pulse wave velocity (PWV) results. Pooled analysis showed no significant differences in the change in PWV between the SGLT-2i group and the control group (SMD: 0.11, 95%-CI: − 0.15 ~ 0.37, P = 0.4). Conclusions: The ability of SGLT-2 inhibitors to improve FMD was significant, but there was no significant effect on PWV levels. SGLT-2i was superior to other antidiabetic agents in improving arterial endothelial function.